The effect of inlet temperature towards spray drying of pineapple flesh, pulp and peels: article - Noor Azman, M Faris; Abd Hashib, Syafiza (2017)
This research addresses to study the effect of 130oC, 140oC and 150oC of inlet temperature towards pineapple flesh, pulp and peels powder. The carrier agents that been used was maltodextrin with concentration of 15%, 20% and 25%. The powder was obtained by using spray drying with speed pump 3 was keep constant. The inlet temperature give major impact on the product yield and its flow rate. As inlet temperature increase, the product yield and the flow rate was also increase. After that, the moisture content, titratable acidity and total soluble solids was analyse. The moisture content seem to reduce as the inlet temperature increase. The concentration of maltodextrin found to give effect to the acidity content in the powder. The highest titratable acidity % was found in 15% maltodextrin of pineapple powder. The total soluble solids content in powder found to decrease as the inlet temperature was increase.